Usefulness of transnasal endoscopy where endoscopic submucosal dissection is difficult - Nakamura, Masakatsu; Shibata, Tomoyuki; Tahara, Tomomitsu; Yoshioka, Daisuke; Okubo, Masaaki; Yonemura, Joh; Arisawa, Tomiyasu; Hirata, Ichiro (Gastric cancer : official journal of the International Gastric Cancer Association and the Japanese Gastric Cancer Association, 2011)
Background Early gastric cancer located from the pyloric ring to inside the duodenal bulb (DB) is not easily treated by endoscopic submucosal dissection (ESD). The endoscope needs to be reversed inside the DB to set the resection line at a safe distance from the anal side. Because of the space limitations and limited flexibility of conventional endoscopy (CE), there have been increasing possibilities of complications. Here we report a new ESD technique using a transnasal endoscope (TN-E) that is reversed inside the DB. Methods The subjects were 5 patients with early gastric cancer or adenoma, at locations ranging from the pyloric ring to inside the DB, who were all treated by ESD. We compared results in these patients (TN-E group) with results in five patients with similar disease characteristics who were treated by ESD before July 2008, when the TN-E treatment method was introduced (CE group). In the TN-E group, after marking by CE, we switched the endoscope to the TN-E, and performed the reversing procedure insidethe DB, and cut the anal side of the lesion in a semicircle. We switched back to CE to dissect the remaining half on the oral side. We compared the average resection time, en-bloc resection rate, and safety margin between the TN-E and CE groups. Results Reversing inside the DB and the anal-side procedures proved easy and there were no complications. No bleeding or perforation occurred. The average resection times and en-bloc resection rates were not different between the two groups. All the resections by the TN-E were more than 5 mm away from the tumor margin, whereas a resection rate with a safety margin of more than 5 mm was 80% by CE. Conclusions In conclusion, the TN-E was safe and effective for use inside the DB. ESD using the TN-E contributed to accurate pathological diagnosis, because the size of the resected specimen was sufficient to prevent the burning effect caused by the ESD.